Rural education and Sustainable Rural Development: Arroio Grande District School of Santa Maria/RS / Educação do campo e o Desenvolvimento Rural Sustentável: Escola do Campo do Distrito de Arroio Grande Santa Maria/RS - Ivanio Folmer (Diversitas Journal, 2019)
This text is the result of academic concerns of the authors, who are interested in the subject of Territory; Agroecology and Rural education. This, arises to problematize the relationship of rural education and agriculture-based ecology. The objective of this work was to verify if the Arroio Grande State School of Elementary Education located in the district of Arroio Grande has conception of the agroecological approach in the experience of the school community. This research was done through a bibliographical survey and insertion in the study community. It was verified that the School does not develop in its projects structures capable of strengthening the students' bonds with the local community. The need for a constructive education that is committed to the life and daily life of the student is affirmed, so that this community develops socioeconomically.